Design of Automatic Door Prototype With Intelligent Control Method Using Sensor GY 906 Temperature Based on Arduino Uno - Velkam Siregar (PT Inovasi Pratama Internasional, 2021)
In the current era of globalization, there have been many developments, especially in the realm of technology. Technological advances are expected to facilitate human work. One example is the development of doors, where now there are many doors that operate automatically. Automatic door is a door that will open automatically when someone approaches the door without opening or pushing the door manually. Nowadays automatic doors have been widely used in various places. to facilitate access to a place, the authors conducted research to design automatic doors based on body temperature. This tool is designed using a GY 906 temperature sensor combined with the Arduino uno program.